'To reveal or to conceal'- Disclosure strategies in parents of children with epilepsy in India. (October 2021) - Lachake, Aishwarya V.; Desai, Neelu; Udani, Vrajesh
Highlights: This study offers unique insights into the under-researched topic of disclosure amongst parents of CWE to others outside the immediate family unit. Disclosure practices have improved in parents of CWE in India and well-being and safety of the child has overridden the fear of stigma and discrimination in most. Disclosure is a major step to dispel misconceptions and reduce epilepsy-related stigma at national and global levels Abstract: Purpose: : Disclosure of epilepsy is a relevant but under-researched topic in epilepsy research. This study was done to assess the disclosure strategies in parents of CWE in a developing country with conservative culture. The study also assessed the influence of demographic factors and seizure characteristics on the choice of disclosure. Enablers and barriers behind disclosure and the consequences after disclosure were evaluated. Methods: : A cross-sectional analytical, self-report survey was done in 284 parents of CWE with the help of a semi-structured questionnaire over a 7-month period in the paediatric epilepsy clinic. Disclosure was considered present if epilepsy was revealed to two or more of the five target groups (extended family, school, friends, neighbours, and peers of children). Separate set of questions was given for reasons behind their choice and consequences after disclosure. For continuous variables, unpaired T test or Mann – Whitney U test between group and for categorized variables, Pearson's Chi square test or Fisher's exact test was used. Results: : 92.96 % of 284 subjects disclosed their child's epilepsy while 7.04% concealed. Demographic factors and seizure characteristics did not influence the disclosure choice. Most parents revealed to the extended family followed by teachers. Type of seizure was the commonest information revealed. The main reason behind disclosure was better acceptance of the child followed by safety while main barrier was considering epilepsy as private grief. 92.8% felt their children were better accepted after disclosure. Conclusion: : Disclosure practices have improved in parents of CWE in India and well-being and safety of the child has overridden the fear of stigma and discrimination. This could be the first major step to bring epilepsy out of the shadows at national and global levels.